2011
DOI: 10.4315/0362-028x.jfp-11-023
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Zearalenone, Aflatoxin B1, and Ochratoxin A by Yeast-Based Products: A Method for Quantification of Adsorption Performance

Abstract: A methodology was developed to quantify the efficiency of yeast-based products for adsorption of three mycotoxins: zearalenone (ZEA), aflatoxin B(1) (AFB(1)), and ochratoxin A (OTA). Eight products were tested (yeast cell wall or inactivated yeast). The described experimental protocol based on in vitro tests provided reliable isotherms for each mycotoxin. The most suitable models were the Hill model for ZEA, the Langmuir model for AFB(1), and the Freundlich model for OTA. From these models, original mathematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 24 publications
8
73
0
Order By: Relevance
“…Products containing yeast materials have potential to adsorb mycotoxins due to the physical properties of the yeast cell wall, which has structures that allow for binding of mycotoxins [53,54]. The β-glucan of yeast can from single or triple helix polysaccharide chains which can give adsorptive capacities for mycotoxins through hydrogen and ionic bonding, and van der Waals interactions [55].…”
Section: Possible Mechanism Of Fb1 and Zen Detoxificationmentioning
confidence: 99%
“…Products containing yeast materials have potential to adsorb mycotoxins due to the physical properties of the yeast cell wall, which has structures that allow for binding of mycotoxins [53,54]. The β-glucan of yeast can from single or triple helix polysaccharide chains which can give adsorptive capacities for mycotoxins through hydrogen and ionic bonding, and van der Waals interactions [55].…”
Section: Possible Mechanism Of Fb1 and Zen Detoxificationmentioning
confidence: 99%
“…The most important results obtained until now are summarized in Table 2. Products based on SC (cell wall from baker and brewer yeasts, inactivated baker yeast, or alcohol yeast) was studied, and it was observed that in pH 3, 37 °C and 15 minutes of contact, AFB 1 removal ranged from 2.5% to 49.3%, depending on the concentration of the toxin in the medium, and on the yeast-based products used [66]. These authors also observed a decrease in toxin adsorption as the initial concentration increased, and concluded that adsorption is not a linear phenomenon.…”
Section: Decontamination Of Aflatoxins By Yeastsmentioning
confidence: 99%
“…When isotherms are not linear, comparing the adsorption capacity of yeast products can lead to opposite conclusions, depending on the initial concentration of mycotoxins tested [24].…”
Section: Evaluations Of Different Sources Of Saccharomyces Cerevisiaementioning
confidence: 99%
“…This type of curve indicates that the adsorption increases according to the number of molecules adsorbed, according to [24,32], a cooperative interaction between the adsorbed molecules may have occurred, resulting in a low affinity between yeast and aflatoxin. However, the autolyzed, inactivated and cell wall ferment for the time of 20 mins and the brewer for 10 and 30 mins can be classified as Langmuir, since a behavior close to a concavity can be observed.…”
Section: Evaluations Of Different Sources Of Saccharomyces Cerevisiaementioning
confidence: 99%
See 1 more Smart Citation